Analisis Pengaruh Kemandirian Belajar dan Kemampuan Structure Sense Terhadap Kemampuan Koneksi Matematis Pada Siswa Smk Negeri 2 Pacitan - Widiantari, Reni; Apriyani, Dwi Cahyani Nur; Susanto, Hari Purnomo (Program Studi Pendidikan matematika STKIP PGRI Pacitan STKIP PGRI Pacitan, 2025)
This research aims to determine the influence of independent learning and structure sense abilities on mathematical connection abilities in students at SMK Negeri 2 Pacitan. The research method used is a quantitative approach with an ex-post facto type of research. Data was collected through questionnaires and test instruments. The data analysis used is simple linear regression analysis and simple linear analysis. The results of the research show that independent learning has no effect on students' mathematical connection abilities, while structure sense abilities have a significant effect on students' mathematical connection abilities. However, together independent learning and structure sense abilities influence students' mathematical connection abilities.